Effect of Adding Insulin Transferrin Selenium (ITS) in the Medium on Maturation and Fertilization Rates of Bali Cattle Oocytes - Hikmayani Iskandar; H Sonjaya; M Yusuf (Indonesian Center for Animal Research and Development (ICARD), 2019)
The aim of this study was to determine the effect of adding Insulin Transferrin Selenium (ITS) in the medium on maturation and fertilization rates of Bali cattle oocytes. The ovarium of Bali cows were sliced to produce oocytes, then the collected oocytes were subsequently selected based on their quality. Those oocytes were maturated for 24 hours and then fertilized for 18 hours in the incubators of 5% CO2 with temperature of 38.5ºC. Oocytes were stained using 2% of aceto orcein, and observed under a microscope. This study was divided into four treatments at different addition of ITS in the medium and replicated four times, and analized using a Factorial Complete Randomized Design (CRD)at each treatment. The treatments consisted of P0 as control, P1 (5 ng/ml), P2 (10 ng/ml), and P3 (15 ng/ml). Parameters observed in this study were the stages of oocytes maturation rate that consisted of germinal vesicle (GV), germinal vesicle break down (GVBD), metaphase I (M-I), and metaphase II (M-II), and fertilization rate that consisted of absence of pronucleus (P0), 1 pronucleus (PN1), 2 pronucleus (PN2), and more than two pronucleus (>2PN). The results of this study showed that addition of ITS at 5-15 ng/ml did not effect maturation and fertilization rates of Bali cows oocytes.The conculision of the study is addition of ITS at 5 ng / ml produces the best level of maturation and for the best level of fertilization with addition ITS at 15 ng / ml.